119. Prospective Validation of a 3-Gene Signature for Tuberculosis Diagnosis, Predicting Progression and Evaluating Treatment Response. (26th November 2018) - Warsinske, Hayley; Rao, Aditya; Moreira, Flora Martinez Figueira; Dos Santos, Paulo Cesar Pereira; Liu, Andrew; Scott, Madeleine; Malherbe, Stephanus; Ronacher, Katharina; Walzl, Gerhard; Winter, Jill; Sweeney, Timothy E; Croda, Julio; et al.
Abstract: Background: The World Health Organization (WHO) has identified the need for a nonsputum-based triage test for tuberculosis (TB) that can be used to identify those who need further testing to identify active disease. We investigated whether our previously described 3-gene TB score could identify individuals with active tuberculosis (ATB) prior to seeking care ("active case detection") and how the 3-gene TB score correlated with the timing of disease onset, disease severity, and response to treatment. Methods: This study consisted of a prospective nested case–control trial, Brazil Active Screening Study (BASS; 2016), and re-analysis of data from 2 prospective cohort studies, the Adolescent Cohort Study (ACS; 2005–2007), and the Catalysis Treatment Response Cohort (CTRC; 2010–2013). The BASS case–control subcohort contained 81 adults (ages 20–72 years, 33 ATB, 48 controls). The ACS contained 153 adolescents (ages 12–18 years, 46 ATB, 107 LTBI). The CTRC-contained 138 adults (ages 17–67 years, 100 ATB, 17 other lung disease patients, 21 healthy controls). Results: The 3-gene TB score diagnosed ATB patients with high accuracy: BASS cohort AUC = 0.87 (95% CI = 0.82–0.91, Figure 1A), ACS cohort AUC = 0.86 (95% CI = 0.76–0.97, Figure 1B), and CTRC AUC = 0.93 (95% CI = 0.88–0.97). In the ACS, the 3-gene TB score predicted progression from LTBI to ATB 6 months prior to positive sputum test (AUC = 0.86; 95% CI = 0.79–0.92, Figure 1B). In the CTRC, the 3-gene TB score correlated with glycolytic activity ratio of PET-CT at baseline (correlation = 0.54, P = 3.98 × 10 −8, Figure 1C) and at the end of treatment (correlation = −0.408, P = 3.72 × 10 −5 ). In the CTRC, the 3-gene TB score at baseline predicted the likelihood of prolonged sputum positivity following treatment initiation and treatment response at 6 months ( P = 3.6 × 10 −5 ). Collectively, across all cohorts, the 3-gene TB score identified ATB patients with 90% sensitivity and 70% specificity, and had 99% negative predictive value (NPV) at 5% prevalence. Conclusion: Across 3 independent prospective cohorts, the 3-gene TB score closely approaches the WHO target product profile benchmarks for non-sputum–based triage test at high NPV. These performance characteristics make it a potential test for ruling out ATB and for monitoring disease status. Disclosures: T. E. Sweeney, Inflammatix, Inc.: Employee and Shareholder, Salary. P. Khatri, Inflammatix Inc.: Board Member, Equity